Knowledge, attitude, and practice of nurses in ICU on preventing ventilator-associated pneumonia: a cross-sectional study in Gansu Province, China - Li, Xiarong; Zhang, Xiaoliang; Feng, Yujuan; Yao, Ziyan; Sun, Yi; Zhang, Lingna; Zhang, Haojun; Wang, Junling (Frontiers in Medicine, 2025)
IntroductionVentilator-associated pneumonia (VAP) is a common and life-threatening complication in ICU patients, with its occurrence closely related to ICU nurses’ knowledge, attitudes, and practices. This study aimed to investigate the current status and influencing factors of ICU nurses’ knowledge, attitudes, and practices regarding VAP prevention in Gansu Province, and to provide a basis for improving the effectiveness of VAP prevention.MethodsA stratified random sampling method was used to select 600 ICU nurses from 24 hospitals in Gansu Province as study participants. Data related to VAP prevention among the nurses were collected through a questionnaire survey and statistically analyzed using SPSS 26.0.ResultsThe overall score of nurses on VAP prevention was 113.92 ± 8.472, with the lowest score in the knowledge dimension (7.66 ± 1.200) and higher scores in the attitude (28.67 ± 3.528) and practice (77.59 ± 5.839) dimensions. Factors such as region, ICU type, number of training sessions, and years of work experience significantly affected VAP prevention knowledge, attitudes, and practices. The knowledge scores of nurses in the Lanzhou and Zhangye regions were significantly higher than those in other regions, and nurses in comprehensive ICUs had higher VAP knowledge scores. Additionally, nurses who participated in four or more VAP prevention training sessions had significantly higher scores in all dimensions compared to those with fewer training sessions. A significant positive correlation was found between knowledge, attitudes, and practices related to VAP prevention.ConclusionICU nurses in Gansu Province performed better in the attitudes and practices of VAP prevention, but there is still room for improvement in their knowledge. Regional differences, ICU type, and the number of training sessions are important factors influencing VAP prevention and control abilities. The study suggests that enhanced training in VAP prevention and control knowledge can help improve nurses’ attitudes and practical skills. To improve the effectiveness of VAP prevention, hospitals should focus on strengthening training in areas with weaker knowledge and increasing the frequency of training sessions.